Activated Carbons and Their Evaluation in Electric Double Layer Capacitors - Krzysztof Kierzek; Grażyna Gryglewicz (Molecules, 2020)
This review presents a summary of the manufacturing of activated carbons (ACs) as electrode materials for electric double layer capacitors. Commonly used techniques of open and closed porosity determination (gas adsorption, immersion calorimetry, X-ray and neutrons scattering) were briefly described. AC production methods (laboratory and industrial) were detailed presented with the stress on advantages and drawbacks of each ones in the field of electrode materials of supercapacitor. We discussed all general parameters of the activation process and their influence on the production efficiency and the porous structure of ACs. We showed that porosity development of ACs is not the only factor influencing capacity properties. The role of pore size distribution, raw material origin, final carbon structure ordering, particles morphology and purity must be also taken into account. The impact of surface chemistry of AC was considered not only in the context of pseudocapacity but also other important factors, such as inter-particle conductivity, maximal operating voltage window and long-term stability.